Development and optimization of a simian immunodeficiency virus (SIV) droplet digital PCR (ddPCR) assay - Long, Samuel (PLoS One, 2020)
Accurate and sensitive quantification of rebound competent HIV that persists despite combination antiretroviral treatment (cART), including in latently infected cells (i.e., viral reservoir), is critical for evaluating cure strategies for decreasing or eliminating this reservoir. Simian immunodeficiency virus (SIV)-infected Rhesus macaques are an important non-human primate (NHP) system for studying potential cure strategies as they model many key aspects of human HIV-infection including the persistence of a latent viral reservoir in resting memory CD4+ T cells in animals receiving prolonged cART. In this report, we describe the design and testing of a sensitive SIV droplet digital PCR (ddPCR) assay through exploring the combination and optimization of different probe systems (including single, double quencher probes and minor groove binder (MGB) probes) and reaction conditions to eliminate background signal(s), ensure distinct target signal cluster separation from non-target signals, and enable detection and quantification of low level authentic target signals. Similar reaction conditions and assay validation procedures can be explored for potential development of additional assays for other applications that require sensitive detection of low-level targets in a large background of nucleic acid input derived from cell or tissue sources.